Comparison of scores in psychological measurement tools of 8th grade Iranian students from various income levels - Sahranavard, Maryam; Hassan, Siti Aishah; Elias, Habibah; Abdullah, Maria Chong (Rushing Water Publishers Ltd, 2013)
The main objective of the present study was to compare the performance of school children that belong to high, medium and low family income in student’s psychological factors, namely: general self-concept, science self-concept, self-efficacy, science self-efficacy, self-esteem, anxiety and science anxiety. The participants in the study consisted of 680 lower secondary school children, with 317 male and 363 female from Tehran and Shahriar City, the Province of Tehran, Iran. Five valid and reliable instruments were used, namely: Self-concept Attribute Attitude Scale, State-Trait Anxiety Inventory, Coopersmith Self-Esteem Inventory, General Self-Efficacy questionnaire and Science Self-Efficacy questionnaire. Descriptive statistics and MANOVA were used to analyze the data. The result showed that there are significant differences between the three groups in science anxiety, self-esteem and self-efficacy (p < 0.01).